Der Fremde im Königreich der Dänen. Das Wort, der Diskurs und die Fremdheit in Bronisław Świderskis Roman Słowa obcego - de Bończa Bukowski, Piotr (Folia Scandinavica Posnaniensia, 2019)
The prose work of the Polish exile writer Bronisław Świderski, who has been living in Denmark since 1970, explores strangeness – an important topic of modern literature. Świderski addresses strangeness not only as an individual experience, but also as a social problem. In this article, I would like to take a closer look at the analysis of foreignness and the psyche of an immigrant in Świderski’s award-winning novel Słowa obcego (1998). From many problems addressed in the novel, which are directly or indirectly connected with strangeness, I want to take out one aspect. At this point I will be interested in the relationship between language (discourse) and strangeness.